The Role of Village-Owned Enterprises in Increasing Corn Agricultural Production and Community Welfare in Talabosa Village - Mengkido, Abner; Paembonan, Laendatu; Muis, Armin; Nurnaningsih, Nurnaningsih; Armin, Armin (Transpublika Publisher, 2025)
This research aims to determine the role of Village-Owned Enterprises (BUMDes) in enhancing agricultural potential and community welfare. The analytical method used in this research is qualitative method with data collection techniques through observation, direct interviews, interactive analysis conducted continuously through various stages including reduction, data presentation, verification and conclusion drawing. The research results show that the role of BUMDes in the community provides a positive impact because the existence of BUMDes can: 1) Increase agricultural productivity 2) Provide socialization or training programs for planting and fertilizing. 3) Provide convenience to the community in obtaining fertilizers, pesticides, seeds. 4) Increase community income and Original Village Revenue. 5) Help the community in developing businesses through access to capital.